2021
DOI: 10.1002/chem.202101995
|View full text |Cite
|
Sign up to set email alerts
|

Facile Approach to C‐Glucosides by Using a Protecting‐Group‐Free Hiyama Cross‐Coupling Reaction: High‐Yielding Dapagliflozin Synthesis

Abstract: This work represents another step in the effort to use glycals (1,2unsaturated derivatives of carbohydrates) as donor synthons for transition metal-catalyzed arylation reactions. We have employed a novel 1-silyl derivative of d-glucal, which was obtained as ab enchstable solid and could therefore be used conveniently.F or its preparation, we have used at ransient protection with MOP groups, which we developed previously,a nd therefore we could access the key synthon in its unprotected form. Ta king advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Moreover, the NOE spectrum of compounds 13 and 15 showed a clear interaction between the protons H‐1 and H‐5 due to syn‐relationship, which further confirms the stereochemistry of glycoside as β anomer [4b,7] . Moreover, the analytical data of compound 15 is in agreement with the literature report [13] …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the NOE spectrum of compounds 13 and 15 showed a clear interaction between the protons H‐1 and H‐5 due to syn‐relationship, which further confirms the stereochemistry of glycoside as β anomer [4b,7] . Moreover, the analytical data of compound 15 is in agreement with the literature report [13] …”
Section: Resultssupporting
confidence: 88%
“…[4b,7] Moreover, the analytical data of compound 15 is in agreement with the literature report. [13] Further, we explored the regioselective synthesis of C-2 nitro aryl enones from aryl enones via nitration reaction (Scheme 7). The aryl enones 3 a and 3 e were treated with a mixture of tetrabutylammonium nitrate and trifluoroacetic anhydride in DCM at 40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Since β- C -glucosides broadly exist in drug molecules, this method should provide meaningful synthetic applications in medicinal chemistry. When the silyl-protecting groups were changed to benzyl groups, further transformation with DMDO and Superhydride was conducted to afford the desired C -glycosides 11 with highly controlled α-configuration. , Collectively, we have demonstrated that our newly developed method could be applied to generate structurally diverse and functionalized C -glycosides rapidly and efficiently.…”
Section: Resultsmentioning
confidence: 87%
“…Aligned with our focus on the precise preparation of glycopeptides and the modification of complex peptides [53][54][55][56] , we intend to leverage the robust palladium-catalyzed Suzuki-Miyaura coupling method for efficient synthesis of glycal amino acids or glycal peptides (Fig. 3), an area with limited exploration and established synthesis methods 32 . Under standard reaction conditions, both fully protected and partially protected phenylalanine derivatives, including Boc-L-Phe(4-Br)-OMe (16a), Boc-L-Phe(4-Br)-OH (16b), and NH 2 -L-Phe(4-Br)-OMe (16c), yielded the corresponding products in 94%, 53%, and 58% yields, respectively.…”
Section: Reaction Scopementioning
confidence: 99%
“…Transition-metal-catalyzed cross-coupling reactions have firmly established themselves as indispensable tools in modern organic synthesis. Notable progress has also been made in constructing C1-substituted glycals through transition-metal-catalyzed Stille [24][25][26][27][28][29] , Negishi 30 , Hiyama-Denmark 17,31,32 , and Heck 33,34 cross-coupling reactions. Among them, the environmentally friendly Suzuki-Miyaura cross-coupling reaction stands out as a crucial tool in glycal-based cross-coupling.…”
mentioning
confidence: 99%